Chief executive officer power and initial public offering underpricing: Examining the influence of demand‐side cultural power distance. (11th October 2021) - Krause, Ryan; Chen, Juanyi; Bruton, Garry D.; Filatotchev, Igor
Abstract: Research Summary: Initial public offering (IPO) underpricing reflects the inability of early investors to capture the full value of an entrepreneurial firm. IPO firms can potentially limit underpricing by signaling wealth protection through lower chief executive officer (CEO) power. Such signaling is particularly challenging for many IPO firms, though, because for those doing business in high‐power‐distance cultures, CEO power can also signal wealth creation, making CEO power a mixed signal for IPO investors. Drawing on signaling theory, we argue that CEO power is positively associated with IPO underpricing, but this relationship weakens for IPO firms doing business in countries with high cultural power distance because the information signaled becomes less clear. The signaling impact of both CEO power and demand‐side cultural power distance weakens, however, when underwriter reputation offers a substitute signal. Managerial Summary: This research offers new knowledge for IPO corporate governance practitioners, such as entrepreneurs, venture capitalists, underwriters, and regulators. Specifically, our research demonstrates that the power dynamic in the upper echelons has implications for demand‐side legitimacy or making U.S.‐listed firms more legitimate with international customers. As a result, stockholders and securities analysts who balk at the consolidation of CEO power should consider the potential benefits that such consolidation of power might grant the firm when competing in different cultural environments associated with foreign markets.